Correlation of microstructural and corrosion characteristics of quaternary shape memory alloys Cu-Al-Ni-X (X=Mn or Ti) - Saud, S. N. (2015)
The effects of different contents (0.4%, 0.7%, and 1.0%, mass fraction) of Mn or Ti additions on the micro structure, shape memory effect and the corrosion behaviour of Cu–Al–Ni shape memory alloys were studied by field emission scanning electron microscopy, transmission electron microscopy, X-ray diffraction, differential scanning calorimetry and electrochemical and immersion tests in NaCl solution. It was observed that the microstructure, shape memory effect and corrosion characteristics are highly sensitive to the composition variations. It was found that the highest strain recovery was with 0.7% addition of Mn or Ti. This may be attributed to the presence of precipitation with a high volume fraction and the grain refinement. The electrochemical test showed that the formation of oxide layers in both Cu–Al–Ni–Mn and Cu–Al–Ni–Ti shape memory alloys (SMAs) provided good passivation which enhanced the corrosion resistance of the alloys. Immersion test showed that in Cu–Al–Ni–Mn– SMAs, pitting corrosion occurred through feebleness in the oxide layer. A corrosion product adjacent to the pits was rich in Al/Mn oxide and depleted in Cu while inside of the pit it was rich in Cu. In Cu–Al–Ni–Ti– SMAs, localized corrosion occurred on the surface of the specimens and dealuminization attack was also observed in the matrix.